Implikasi Hukum Perpindahan Pengawasan Aset Kripto dari Bappebti ke OJK terhadap Pelaku Industri dan Investor: (A Comparative Study) - Hidayat, Beni Darmawan; Sebyar, Muhamad Hasan (LPPM Universitas Sains dan Teknologi Komputer, 2024)
This research discusses the legal implications for industry players and investors arising from the transition of cryptocurrency supervision in Indonesia, which involves the transfer of authority from the Commodity Futures Trading Supervisory Agency (Bappebti) to the Financial Services Authority (OJK) under the Financial Sector Development and Strengthening Law. This transfer of authority has urgency in terms of improving stability, transparency, and consumer protection in the financial sector and all types of financial assets including crypto assets to be supervised by a single body that has sufficient capacity and competence. This research aims to analyze the legal implication of this change in authority for industry players and investors or consumers. This scientific research uses normative research methods, which include statue approach as the basis for research. The findings of this research indicate that the transfer of supervisory authority over crypto assets has significant legal implications for industry players and investors alike. While this transition is expected to enhance legal certainty and consumer protection, the inherent risks associated with crypto investments, particularly market volatility, remain substantial. Therefore, prompt adaptation, improved coordination between the OJK and Bappebti, and comprehensive investor education are crucial to mitigate risks and ensure the successful implementation of the new regulations.